Effects of Nutrient-Fortified Milk-Based Formula on the Nutritional Status and Psychomotor Skills of Preschool Children - Mavil May C. Cervo; Diane S. Mendoza; Erniel B. Barrios; Leonora N. Panlasigui (Journal of Nutrition and Metabolism)
This randomized, single-masked, controlled trial examined the effects of nutrient-fortified milk-based formula supplementation on nutritional status, nutrient intake, and psychomotor skills of selected preschool children with mean age of 4.10 ± 0.14 years. The study participants were divided equally into three major groups, normal, underweight, and severely underweight based on WHO-Child Growth Standards, and were further divided into two groups: fortified milk group who was given two glasses of fortified milk (50 g of powdered milk/serving) a day for twelve weeks in addition to their usual diet and the nonintervention group who was not given fortified milk and thus maintained their usual intake. Anthropometric measurements, dietary intake, and psychomotor developmental score were analyzed. Results showed that consumption of two servings of fortified milk a day for twelve weeks significantly increased the height of preschool children by 1.40 cm, weight by 1.35 kg, body mass index by 0.96 kg/m2, mid-upper arm circumference by 0.66 cm, and psychomotor scores by 13.74% more than those children who did not consume fortified milk (p<0.0001). Hence, fortified milk-based supplement in the diet of preschool children improved overall nutritional status, nutrient intake, and performance in psychomotor scale. This study is registered in Philippine Health Research Registry: PHRR140923-000234.